2019
DOI: 10.1080/13685538.2019.1650906
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar prostate thermotherapy for the improvement of chronic prostatitis symptoms and ejaculation problems

Abstract: This study aims to evaluate the efficacy of the new bipolar radiofrequency thermotherapy device (TEMPRO) on urinary and sexual functions in patients with chronic prostatitis. Between April 2017 and September 2018, 42 male patients with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) were included. The patients had received at least 6 months of treatment via conventional medical treatments. NIH-Chronic Prostatitis Symptom Index (CPSI), International Index of Erectile Function-Erectile Function part (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…First, TEMPRO is intended to promote ablation and coagulation necrosis of the prostate tissue with a specially designed smaller urethral catheter containing six heat rings at its tip. In addition, a recent study of patients with chronic prostatitis has shown that thermotherapy does not affect sexual function (Diri & Gul, 2019). In addition, TUNA is not suitable for prostates larger than 75 ml (Chapple, Issa, & Woo, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, TEMPRO is intended to promote ablation and coagulation necrosis of the prostate tissue with a specially designed smaller urethral catheter containing six heat rings at its tip. In addition, a recent study of patients with chronic prostatitis has shown that thermotherapy does not affect sexual function (Diri & Gul, 2019). In addition, TUNA is not suitable for prostates larger than 75 ml (Chapple, Issa, & Woo, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The most important advantage of TEMPRO thermoablation is the application of the procedure to the prostate tissue, performing the procedure with local anaesthesia and not developing complications in the short term. In addition, a recent study of patients with chronic prostatitis has shown that thermotherapy does not affect sexual function (Diri & Gul, 2019). Comparison of the heat-based minimally invasive methods for BPH is shown in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…The internal administration of TCM can reduce prostate inflammation without increasing the incidence of adverse reactions in the short term. [10] In addition, heat therapy, [11] acupuncture, enema, and other external therapies improve symptoms. As an alternative therapy, TCM treatment based on syndrome differentiation and acupuncture can be combined with other treatment methods to further exert a synergistic effect, and massage and other traditional methods can also be used in the treatment process and daily preventive strategies.…”
Section: Tcm Can Affect Immune-mediated Inflammatory Factors To Reduc...mentioning
confidence: 99%
“…It does not need to be applied in operating room conditions; patients can be discharged on the same day. The same device can be used in the treatment of chronic prostatitis by changing the temperature and time setting 18 . The early postoperative complication rate is very low, and therefore it can be considered as a suitable treatment option, especially for elderly patients with a high anesthesia risk and in cases where possible complications of other invasive treatments are to be avoided 19 .…”
Section: Discussionmentioning
confidence: 99%